Unveiling Racism: A Study of Discrimination in Such a Fun Age - Aisyah Andina Ayu Sekar Lestari (Morphosis: Journal of Literature, 2024)
The aim of this study is to portray the issue of discrimination under racism that the main character experienced as a black woman in Such a Fun Age. It is a novel that is written by Kiley Reid which published in 2019. This study focused on the potrayal of discrimination under racism through the main character’s experience and the response from the main character towards the discrimination. This study conducted analysis using qualitative methods, as well as the theory of race and racism under the title “The Idiom of Race” from Michael Banton which is summarized in a theory book entitled “Theories of Race and Racism: A Reader” (2000) that was edited by John Solomos and Les Back and used by the writer in analyzing the data found. Based on the findings and analysis from the data found, the results shows that there are acts of discrimination in the form of deemed unearthly, deemed ineligible, and deemed as a criminal, which position the main character in the difficulty of living her life as a black woman. The acts of discrimination in this novel resulted that it has bothered the equality between races and differentiated other race unfairly. Keywords: discrimination, race, racism.